NUMERICAL STUDIES CORRELATING THE HYDRODYNAMIC RESPONSES OF DEEPWATER FPSOS WITH SHALLOW WATER MODEL RESULTS - MATTHEW , GUAN ZHEN HWA (2018)
A study is conducted to assess the effects of parameters influencing the hydrodynamic responses of a deepwater Floating Production Storage Offloading (FPSO) platform and its mooring lines when using model test measurements in shallow water wave basins.